Cold War Reckonings Authoritarianism and the Genres of Decolonization - Watson, Jini Kim (Fordham University Press, 2021)
How did the Cold War shape culture and political power in decolonizing countries and give rise to authoritarian regimes in the so-called free world? Cold War Reckonings tells a new story about the Cold War and the global shift from colonialism to independent nation-states. Assembling a body of transpacific cultural works that speak to this historical conjuncture, Jini Kim Watson reveals autocracy to be not a deficient form of liberal democracy, but rather the result of Cold War entanglements with decolonization. Focusing on East and Southeast Asia, the book scrutinizes cultural texts ranging from dissident poetry, fiction, and writers' conference proceedings of the Cold War period, to more recent literature, graphic novels, and films that retrospectively look back to these decades with a critical eye. Paying particular attention to anti-communist repression and state infrastructures of violence, the book provides a richaccount of several U.S.-allied Cold War regimes in the Asia Pacific, including the South Korean military dictatorship, Marcos' rule in the Philippines, illiberal Singapore under Lee Kuan Yew, and Suharto's Indonesia. Watson's book argues that the cultural forms and narrative techniques that emerged from the Cold War-decolonizing matrix offer new ways of comprehending these histories and connecting them to our present. The book advances our understanding of the global reverberations of the Cold War and its enduring influence on cultural and political formations in the Asia Pacific. Cold War Reckonings is available from the publisher on an open-access basis.